Monetary policy transmission to consumer financial stress and durable consumption - Dimitris Georgarakos; Konstantinos Tatsiramos (Center for Economic Studies and ifo Institute (CESifo), 2019)
We examine the effects of monetary policy on household self-assessed financial stress and durable consumption using panel data from eighteen annual waves of the British Household Panel Survey. For identification, we exploit random variation in household exposure to interest rates generated by the random timing of household interview dates with respect to policy rate changes. After accounting for household and month-year-of-interview fixed effects, we uncover significant heterogeneities in the way monetary policy affects household groups that differ in housing and saving status. In particular, an increase in the interest rate induces financial stress among mortgagors and renters, while it lessens financial stress of savers. We find symmetric effects on durable consumption, mainly driven by mortgagors with high debt burden or limited access to liquidity and younger renters who are prospective home buyers.
Keywords: G21; E21; 330; monetary policy; mortgage debt; debt burden; financial stress; consumption